Associations of multidimensional health literacy with reported oral health promoting behaviour among Slovak adults: a cross-sectional study - Eva Cepova; Martina Cicvakova; Peter Kolarcik; Neda Markovska; Andrea Madarasova Geckova (BMC, 2018)
Abstract Background Modification of health literacy (HL) is an important factor for improving and maintaining oral health. The aim of the study is to examine the association of HL with oral health-promoting behaviour (OHPB) and assess possible mediating effects of HL on the impact of socioeconomic status on OHPB. Methods A cross-sectional questionnaire survey on the Slovak general adult population (N = 360, mean age 39) was conducted in 2014 and 2015. The association of HL (9 domains of the Health Literacy Questionnaire) and OHPB was analysed using logistic regression models adjusted for gender, age and educational level. Testing the mediating effect of HL domains between education attainment and OHPB was performed using the Sobel test. Results Women and respondents with higher education reported better OHPB. Regular tooth-brushing is associated with better HL in five domains: Feeling understood and supported by healthcare provider, Having sufficient information to manage my health, Activelymanaging my health, Social support for health, Appraisal of health information (Odds ratios (ORs) from 1.64 to 2.33, p < 0.05). Using interdental tools is in association with better HL in two domains: Feeling understood and supported by a healthcare provider and Having sufficient information to manage my health (ORs 1.71 to 1.80, p < 0.05). Respondents who visited a dentist for prevention score higher in Social support for health (OR 1.79, p < 0.05). Using a tongue scraper and single brush and reporting gums bleeding is notstatistically significantly associated with HL. Mediation was confirmed between the effect of respondents' education on using fluoride toothpaste - mediated respondent's ability to find good health information. Frequency of tooth-brushing and using interdental hygiene aids were both mediated by patient's sufficient information to manage health. Conclusions Our results indicate HL to be an important factor related to good oral health, and HL should be considered when planning oral health interventions.